Comparing APACHE II, APACHE IV, SAPS II, and SOFA Predictive Power in Poisoned Patients Admitted to the Intensive Care Unit - Silakhori, Samaneh; Dadpour, Bita; Khadem-Rezaiyan, Majid; Sedaghat, Alireza; Mirzakhani, Farzad (International Journal of Medical Toxicology and Forensic Medicine, 2020)
Background: This study aimed to assess the performance of the Acute Physiology and Chronic Health Evaluation (APACHE) II, APACHE IV, Simplified Acute Physiologic Score (SAPS) II, and Sequential Organ Failure Assessment (SOFA) scores in predicting mortality rate in poisoning patients admitted to an intensive care unit (ICU). Methods: This cross-sectional study was performed on all admitted patients in the poisoning ICU of Imam Reza Hospital, Mashhad City, Iran. All patients were evaluated for three consecutive days since admission time and then every two days until discharge from ICU or death. The scoring systems mentioned above were calculated and analyzed by MedCalc statistical software version 18.9.1 and SPSS version 16. Results: Overall, 150 patients were studied, out of whom 67% (101) were male. Their mean±SD age was 41.6±18.9 years. In their whole hospitalization period, APACHE II (79.5%), SAPS II (78.7%), APACHE IV (78.4%), and SOFA (72.9%) were the most precise measures. On the first day of admission APACHE II (77.4%), on the second day, APACHE II (83.1%), on the third day, APACHE II (90.7%), and on the fifth day, SOFA (81.6%) were the most precise measures. Conclusion: All four systems have acceptable discriminatory power for poisoned patients. However, it seems that APACHE II can be used for mortality prediction, especially in the early days of admission.